The Effect of Interest Groups on the Labour Market. Trade Unions in Poland - Woźniak-Jęchorek, Beata (Studia Oeconomica Posnaniensia, 2014)
The main goal of this paper is to present the theory of interest groups from the perspective of the labour market and illustrate it by the activities of trade unions in Poland. The theoretical background of this study is the theory of M. Olson, classified under the new institutional economics. An interest group is defined by M. Olson as "a number of individuals who have a common interest" [Olson 2012, p. 16]. In mainstream economics it is assumed that individuals are rational and focused on their own interests. However, in the theory of groups it has been proved that, despite the rational approach, the group will not automatically act in the interest of the whole community. The activities of trade unions might be an example of this. The paper presents the assumptions of the concept of interest groups included in public choice theory, showing the categories of interest groups from the perspective of the Polish labour market, and finally specifies the place of trade unions in Poland compared to selected OECD countries.